(untitled) (International Journal of Engineering Materials and Manufacture, 2022)
Ti-alloy represents a significant metal portion of aircraft structural and engine components for high reliability. Surface integrity is one of the most relevant parameters used for evaluating the quality of finish machined surfaces. The residual stress and surface alteration with each layer and depth of work hardening by machining Ti-alloy are critical due to safety and sustainability concerns. Residual stresses, white layers well microstructural alterations can be figured out to improve surface qualities of end products. Many parameters such as cutting speed, feed rate, depth of cut affect the machined surface quality particularly surface fisnish. This article provides details of lathe turning for investigation of surface roughness for varying cutting parameters. An attempt has been made to search for best ranges of cutting regimes that could produce best surface roughness for machining Ti-6Al-4V alloy using uncoated cutting tool. Taylor-Hobson device is used to measure the surface roughness on the machined workpieces. In this project three series of experimentaions were carried out and a total of 16 steps of operations in each series are performed for determining the surface roughness. Real life experimental investigation has allowed to express the results in graphical form (using tabulated data) that has suggested best ranges of cutting regimes (parameters) for obtaining the best ranges of surface roughness for machining Ti-6Al-4V using uncoated carbide tool. The work has indicated to investigate the science of bulk flow, particularly the plastic deformation, for difficult to machine materials, at a much higher temperature. Behaviour of cutting tool materials for high speed cutting is another isuue to develop.